Production of hyperimmune sera: a study of digestion and fractionation methodologies for the purification process of heterologous immunoglobulins. (2nd January 2023) - da Costa, Camila Braz Pereira; Carvalho, Vanessa Ramos de; Ferreira, Leide Lene Coelho; Mattos, Jorge Luiz Coelho; Garcia, Leila de Mendonça; Antunes, Marcia de Souza; Martins, Francislene Juliana; Ratcliffe, Norman A.; Cisne, Rafael; Castro, Helena C.
Abstract: Several scientific studies to evaluate the process of digestion and fractionation of immunoglobulins have been carried out in order to improve the production of hyperimmune sera. Today, quality, safety, and production efficiency, along with the development of optimized, robust, and cost-effective processes are priorities. Thus, this work analyzed previous studies of enzymatic digestion of heterologous immunoglobulin G, as well as studies of protein fractionation with caprylic acid, to verify the experimental conditions and their impacts on production processes. The establishment of possible variables; such as concentration, pH, time, and temperature; may allow optimization of the production of hyperimmune sera. Most of the digestive processes evaluated took place at 37° C, pH 3.2, with times longer than 90 minutes, and pepsin inactivation between pH 7.0 and 7.2, while fractionation with caprylic acid used a concentration of 5%, 37° C, and pH 5.0–5.8, for 60 minutes. This work aimed to establish, the ideal conditions to be applied in the production of hyperimmune sera.